Maturation of the cytochrome cd1 nitrite reductase NirS from Pseudomonas aeruginosa requires transient interactions between the three proteins NirS, NirN and NirF. Issue 3 (27th June 2013) - Nicke, Tristan; Schnitzer, Tobias; Münch, Karin; Adamczack, Julia; Haufschildt, Kristin; Buchmeier, Sabine; Kucklick, Martin; Felgenträger, Undine; Jänsch, Lothar; Riedel, Katharina; Layer, Gunhild
Abstract : The periplasmic cytochrome cd 1 nitrite reductase NirS occurring in denitrifying bacteria such as the human pathogen Pseudomonas aeruginosa contains the essential tetrapyrrole cofactors haem c and haem d 1 . Whereas the haem  c is incorporated into NirS by the cytochrome c maturation system I, nothing is known about the insertion of the haem d 1 into NirS. Here, we show by co-immunoprecipitation that NirS interacts with the potential haem d 1 insertion protein NirN in vivo . This NirS–NirN interaction is dependent on the presence of the putative haem d 1 biosynthesis enzyme NirF. Further, we show by affinity co-purification that NirS also directly interacts with NirF. Additionally, NirF is shown to be a membrane anchored lipoprotein in P. aeruginosa . Finally, the analysis by UV–visible absorption spectroscopy of the periplasmic protein fractions prepared from the P. aeruginosa WT (wild-type) and a P. aeruginosa Δ nirN mutant shows that the cofactor content of NirS is altered in the absence of NirN. Based on our results, we propose a potential model for the maturation of NirS in which the three proteins NirS, NirN and NirF form a transient, membrane-associated complex in order to achieve the last step of haem d 1 biosynthesis and insertion of the cofactor into NirS.